Integrating Reproductive Health in Sexual Education: A New Model to Address Global Challenges Among Adolescents - Andi Nurzakiah Amin; Samsiana Samsiana; Andi Atssam Mappanyukki (Musamus Journal of Physical Education and Sport (MJPES), 2024)
Objectives. This study developed a comprehensive sexual education model to reduce unwanted pregnancies and sexually transmitted infections, and improve adolescents' knowledge and life skills. Materials and Methods. This study involved 35 participants, consisting of 20 adolescents (12-19 years old) and 15 educators (25-50 years old) from 3 schools. Qualitative research method was chosen to explore experiences and views related to the integration of reproductive health in sexual education. The sample was selected by purposive sampling, and data were collected through in-depth interviews and focus group discussions. Data were analysed using thematic techniques to identify patterns and themes from the interviews and observations. Results. The results of the analysis showed that before the implementation of the sexual education model, adolescents had limited and inconsistent knowledge about reproductive health. After four months of implementation, many adolescents reported increased understanding and confidence in protecting themselves. Some students considered the materials too formal and experienced problems accessing information outside of school. Educators rated the curriculum as effective but faced challenges in addressing student discomfort and resource limitations. Students felt more open and comfortable, but wanted more discussion and practice. Teachers and facilitators suggested improving the curriculum, materials and training. Conclusion. Comprehensive sexual education programmes increase students' knowledge, but require development of interactions, policy support, and teacher training. Keywords. Reproductive Health, Sexual Education and Adolescents